2014
DOI: 10.1586/14787210.2014.942284
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile: improving the prevention paradigm in healthcare settings

Abstract: Clostridium difficile infection (CDI) is a major public health problem worldwide with significant morbidity and mortality that is spread by spores and fecal oral transmission. A variety of risk factors have been identified. Some risk factors such as age, are not amenable to change, while others such as antimicrobial utilization have resulted in broadly implemented antimicrobial stewardship programs. New risk factors are emerging such as proton pump inhibitor (PPI) use, irritable bowel disease (IBD) and obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 155 publications
0
7
0
Order By: Relevance
“… 29 Studies have shown that unrecognized cases of CDI are admitted to health care facilities or transferred from one facility to another and may spread it within a facility via health care workers’ hands. 30 , 31 However, CDI can be prevented. Environmental contamination stems from the fecal–oral transfer of C. difficile spores from the patient to the health care workers’ hands and medical equipment leading to the ingestion of spores by other patients.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Studies have shown that unrecognized cases of CDI are admitted to health care facilities or transferred from one facility to another and may spread it within a facility via health care workers’ hands. 30 , 31 However, CDI can be prevented. Environmental contamination stems from the fecal–oral transfer of C. difficile spores from the patient to the health care workers’ hands and medical equipment leading to the ingestion of spores by other patients.…”
Section: Discussionmentioning
confidence: 99%
“…This form of obesity can be transmitted, for example, from one member of a family to another and can simulate the "hereditary" nature of the disease. According to some authors, the most radical way to prevent and treat such forms of obesity is to transplant the microbiome from a healthy donor [25][26][27][28].…”
Section: The Stage Of Digestion and Assimilation Of Nutrient Digestiomentioning
confidence: 99%
“…A recent study found antiproliferative effects of the cell-free filtrate and the cell-free lyophilized filtrate of LAB (Pediococcus pentosaceus, Lactobacillus plantarum, and Weissella confusa) on human colorectal adenocarcinoma cell (Knecht et al, 2014). Increasing evidence also suggested that LAB including L. casei (Bignardi, 1998), L. rhamnosus (Assallo et al, 2014), L. acidophilus, all have the abilities of inhibiting tumor growth in rodents. Kahouli et alreported thatL.…”
Section: Lab In Preventing Colon Cancermentioning
confidence: 99%